Recent Progress on Advanced Flexible Lithium Battery Materials and Fabrication Process - Mi Zhou; Daohong Han; Xiangming Cui; Jingzhao Wang; Xin Chen; Jianan Wang; Shiyi Sun; Wei Yan (Nanomaterials)
Flexible energy storage devices have attracted wide attention as a key technology restricting the vigorous development of wearable electronic products. However, the practical application of flexible batteries faces great challenges, including the lack of good mechanical toughness of battery component materials and excellent adhesion between components, resulting in battery performance degradation or failure when subjected to different types of deformation. It is imperative to develop flexible batteries that can withstand deformation under different conditions and maintain stable battery performance. This paper reviews the latest research progress of flexible lithium batteries, from the research and development of new flexible battery materials, advanced preparation processes, and typical flexible structure design. First, the types of key component materials and corresponding modification technologies for flexible batteries are emphasized, mainly including carbon-based materials with flexibility, lithium anode materials, and solid-state electrolyte materials. In addition, the application of typical flexible structural designs (buckling, spiral, and origami) in flexible batteries is clarified, such as 3D printing and electrospinning, as well as advanced fabrication techniques commonly used in flexible materials and battery components. Finally, the limitations and coping strategies in the practical application of flexible lithium batteries are discussed, which provides new ideas for future research.